PARTICULAR ASPECTS OF SOIL POROSITY AND CAPILLARITY IN PRACTICE - Rajabova, Mahliyo Mahmudovna; Joʻraqulov, Fazliddin Faxriddinovich; Eshpo‘latov, Jo‘rabek (Educational Research in Universal Sciences, 2024)
Explores capillary dynamics in fine-textured soils (clay, silt), emphasizing the influence of particle size and surface characteristics on water ascent against gravity. Investigates less-explored aspects of capillarity in coarse-textured soils (sand), uncovering implications for water availability, retention, and plant response. Analyzes the intricate relationship between pore size distribution and capillary action, offering insights into how variations impact water retention, infiltration rates, and overall soil hydraulic conductivity. Summarizes practical guidelines and recommendations derived from the study, providing actionable insights for farmers, agronomists, and policymakers to optimize soil and water management practices based on specific capillarity and porosity considerations.